Strategi Guru Dalam Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam di SMP Yayasan Pesantren Modern Adnan - Salim, Agus (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research was conducted with the aim of finding out teacher strategies in improving student learning outcomes in SKI subjects at the Adnan Modern Islamic Boarding School Foundation Middle School. This research uses qualitative methods with the type Field Research. The techniques used to obtain data are interviews, observation and documentation. Meanwhile, the data analysis technique used in this research uses the Miles and Huberman data analysis model which consists of several steps, namely: 1) Collecting data; 2) Reduction data; 3) Displaying data; 4) Drawing conclusions and verifying data. Meanwhile, the data validity technique in this research uses triangulation, namely source triangulation, technical triangulation and time triangulation. The strategies used by teachers to improve student learning outcomes at the Adnan Modern Islamic Boarding School Foundation Middle School are: project-based learning strategies, namely strategies with learning methods that use projects/activities as media. Students will carry out exploration, assessment, interpretation, synthesis and information to produce various forms of student learning outcomes.